Activation of calcineurin underlies altered trafficking of α2 subunit containing GABAA receptors during prolonged epileptiform activity. (January 2015) - Eckel, Ramona; Szulc, Blanka; Walker, Matthew C.; Kittler, Josef T.
Abstract: Fast inhibitory signalling in the mammalian brain is mediated by gamma-aminobutyric acid type A receptors (GABAA Rs), which are targets for anti-epileptic therapy such as benzodiazepines. GABAA Rs undergo tightly regulated trafficking processes that are essential for maintenance and physiological modulation of inhibitory strength. The trafficking of GABAA Rs to and from the membrane is altered during prolonged seizures such as in Status Epilepticus (SE) and has been suggested to contribute to benzodiazepine pharmacoresistance in patients with SE. However, the intracellular signalling mechanisms that cause this modification in GABAA R trafficking remain poorly understood. In this study, we investigate the surface stability of GABAA Rs during SE utilising the low Mg 2+ model in hippocampal rat neurons. Live-cell imaging of super ecliptic pHluorin (SEP)-tagged α2 subunit containing GABAA Rs during low Mg 2+ conditions reveals that the somatic surface receptor pool undergoes down-regulation dependent on N-methyl-d -aspartate receptor (NMDAR) activity. Analysis of the intracellular Ca 2+ signal during low Mg 2+ using the Ca 2+ -indicator Fluo4 shows that this reduction of surface GABAA Rs correlates well with the timeline of intracellular Ca 2+ changes. Furthermore, we show that the activation of the phosphatase calcineurin was required for the decrease in surface GABAA Rs in neurons undergoing epileptiform activity. These results indicate that somatic modulation of GABAA R trafficking during epileptiform activity in vitro is mediated by calcineurin activation which is linked to changes in intracellular Ca 2+ concentrations. These mechanisms could account for benzodiazepine pharmacoresistance and the maintenance of recurrent seizure activity, and reveal potential novel targets for the treatment of SE. This article is part of the Special Issue entitled 'GABAergic Signaling in Health and Disease'. Highlights: We investigate surface stability of GABAA Rs in an in vitro model of Status Epilepticus. Live-cell imaging shows a decrease in surface GABAA Rs in the cell soma. Decrease of somatic GABAA Rs from the surface is mediated by NMDAR activity. In vitro Status Epilepticus induces intracellular Ca 2+ changes. Calcineurin mediates the decrease of somatic GABAA Rs from the surface.